Strategic E-Branding Communication in the Local Government Program: Teras Malioboro - Deslia, Iva Fikrani; Amali, Muhammad Thoyib (Universitas Islam Negeri Raden Intan Lampung, 2026)
In the dynamic landscape of new media, e-branding has become an important strategy for both companies and governmental institutions to foster engagement, cultivate trust, and cultivate a positive brand image. Teras Malioboro is a local government initiative aimed at relocating street vendors from the sidewalks of Jalan Malioboro, while simultaneously positioning itself as a well-organized and innovative shopping destination. However, persistently low visitor numbers have incited protests from traders, highlighting challenges in its branding endeavors. This study investigates how Teras Malioboro employs the seven principles of e-branding through a qualitative case study methodology, utilizing data collected through in-depth interviews, observation, and documentation. The results indicate that community participation, core competency, the dissemination of good ideas, and the maintenance of current content exhibit more effective implementation, whereas ceding control, engaging in dialogue with users, and fostering engagement remain suboptimal due to limited audience participation, low responsiveness to comments, and inadequate interactive communication practices. The findings identify compelling key messages, sufficient human resources, strategic collaborations, and influencer engagement in enhancing e-branding effectiveness. Furthermore, the study extends the e-branding framework by illustrating that classical e-branding principles require contextual adaptation when applied within the setting of local government.